Post a New Question

pre calculus

posted by on .

let f(x)= -x^2 - 1. evaluate f(x)at x=6, -6

  • pre calculus - ,

    f(x)=-x^2-1
    f(6)=-(6)^2-1=-36-1=-37
    f(-6)=-(-6)^2-1=-36-1=37
    So we see that for this particular function, f(6)=f(-6).

    In fact, since f(x) is an even function (consisting of even powers of x), this property of f(x)=f(-x) is true for all values of x.

    You can try out other pairs, such as f(2) and f(-2) to verify this property.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question